THE USE OF PRONOUN IN STRATEGY OF POLITENESS IN TALK SHOW PROGRAM - Andyka Yulia Adha; Sri Minda Murni; Anni Holila Pulungan (Universitas Negeri Medan, 2021)
This qualitative descriptive research deals with The Use of Pronoun in Strategy of Politeness In Talk Show Program. This research observe the Use of Pronoun in Strategy of Politeness In Indonesia Lawyer Club ( ILC) Talk Show Program in some episode. The objectives of this study were to find out the types of politeness strategies are used in personal subject pronoun by the interviewees in Indonesia Lawyer Club ( ILC) Talk Show Program, and to investigate politeness strategies used the personal subject pronoun. The data were taken from the episode of Indonesia Lawyer Club Talk Show Program in 2018 years. The data were collected by downloading the video of Indonesia Lawyer Club Talk Show Program from youtube and then were transcribed. The data were analyzed by qualitative research based on interactive model which is created by Miles and Huberman. The result of the research shown the positive and negative politeness are used in Indonesia Lawyer Club ( ILC) by the same person. The same speaker and the same hearer used the politeness dynamically. It depends on topics/ issue whereas they understand or not in other hand they expert in the material. the researcher found that all types of Politeness Strategies proposed by Brown and Levinson (1987) found in the data. The data of Positive Politeness were consisted of 28 lines (42.42%) which was the highest data from other strategies, while Off Record of Politeness Strategies was obtained as much 18 lines (30.30%), then followed by Negative Politeness of Politeness Strategies was obtained as much 17 lines (22.73%), and the last was Bald on Record with 3 lines (4.55%). Keywords: Politeness strategies, Pronouns, Talkshow Program